Overview of policies towards women scientists in some countries - Anh, Nguyen Lan; Ha, Nguyen Thi Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Today over the world, the rate of involvement of women in scientific research activities does not depend too much on the development status of nations but on policies of every Government towards stimulation for women scientists. International experiences show that many countries and international organizations are highly interested in stimulation and supports for women to participate in scientific research activities and they adopt numerous concrete policies in arrangement of resources for realization of these policies. Code: 20010601